Finding a Balance: How Diverse Dosage Compensation Strategies Modify Histone H4 to Regulate Transcription - Wells, Michael B. (Hindawi Publishing Corporation, 2012)
Dosage compensation balances gene expression levels between the sex chromosomes and autosomes and sex-chromosome-linked gene expression levels between the sexes. Different dosage compensation strategies evolved in different lineages, but all involve changes in chromatin. This paper discusses our current understanding of how modifications of the histone H4 tail, particularly changes in levels of H4 lysine 16 acetylation and H4 lysine 20 methylation, can be used in different contexts to either modulate gene expression levels twofold or to completely inhibit transcription.